Literasi Komunikasi Bahasa Inggris untuk Pekerja Industri di Karawang - Mobit Mobit; Hilmansyah Saefullah; Praditya Putri Utami (Jurnal Pengabdian Pada Masyarakat, 2021)
ENGLISH COMMUNICATION LITERACY FOR INDUSTRIAL WORKER IN KARAWANG. Communication competence in using English for industrial workers in multinational companies will add value to employees and company. Multi-national companies are companies that are managed collaboratively by citizens from several countries. So that, in daily activities it is possible to use the national language or foreign languages. However, not all employees at the level of high, middle, or ordinary employees are competent to communicate in English. This training is designed to provide workers knowledge to communicate in English. Based on a discussion with a representative of the workers, even though the worker was of a multi-national company, he did not get language training carried out by the company, so workers often carry out learning independently using available media. However, due to the absence of a communication partner, his efforts were not maximally successful. There are several activities phases carried out in this program, namely 1) designing activities oriented towards building workers' English competence, 2) preparing activities and communication tools with partners, 3) implementing online learning activities, and finally evaluating activities. The data obtained is the emergence of engagement in worker communication using English. The results shown are: 1) Participants have been able to initiate simple communications in English. 2) Participants have been able to hold short talks individually; and 3) Participants have been able to communicate monologically using short English orally.